2014
DOI: 10.2131/jts.39.173
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression differences in the duodenum of 129/Sv and DBA/2 mice compared with that of C57BL/6J mice

Abstract: -We compared the cadmium (Cd) concentration in the liver and kidney of different strains of mice after exposure to 50 ppm Cd for 30 days via drinking water. Cd concentration in the liver and kidney of C57BL/6J mice were higher than those of 129/Sv and DBA/2 mice. Since orally ingested heavy metals are absorbed in the small intestine and then widely distributed to target tissues, microarray analyses were performed to compare the expression levels of transport-related genes in the duodenum between C57BL/6J mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…We have showed that Cd alters gene expression in several tissues in vivo and cultured cells, including proximal tubular cells 10 11 12 13 14 . In NRK-52E rat proximal tubular epithelial cells, Cd inhibited the gene expression of Ube2d4, a member of the UBE2D (ubiquitin-conjugating enzyme E2D) family 10 .…”
mentioning
confidence: 99%
“…We have showed that Cd alters gene expression in several tissues in vivo and cultured cells, including proximal tubular cells 10 11 12 13 14 . In NRK-52E rat proximal tubular epithelial cells, Cd inhibited the gene expression of Ube2d4, a member of the UBE2D (ubiquitin-conjugating enzyme E2D) family 10 .…”
mentioning
confidence: 99%